Facile and Convenient Synthesis of Triazolopyridazine Derivatives via 1,3-Dipolar Cycloaddition Reaction of Organic Azides† - T. Abu-Orabi, Sultan; Atfah, Adnan; A.S. Ali, Amer; Abu-Shandi, Khaled; Al-Hamdany, Raad (Asian Journal of Chemistry, 2010)
1,3-Dipolar cycloaddition reactions of substituted benzyl azides 1a-t and bis (azidomethyl) benzenes 2a-c with dibenzoylacetylene 3 afforded the corresponding 1H-1,2,3-triazole derivatives 4a-t and 7a-c respectively. Reaction of these triazoles 4a-t and 7a-c with hydrazine hydrate in ethanolic solution was found to produce in high yield the corresponding triazolopyridazine and bis (triazolopyridazine) derivatives 6a-t and 9a-c respectively. The structures of the newly synthesized products 4, 6, 7 and 9 were confirmed from their spectral and analytical data.